RELIGIOUS MODERATION IN INDONESIAN HIGHER EDUCATIONS: Literature Review - Afwadzi, Benny; Miski, Miski (ULUL ALBAB Jurnal Studi Islam, 2021)
This article is an attempt to review various studies on religious moderation or moderate Islam among students in the higher educations in Indonesia. It is written as prompted by the incompleteness of various studies regarding the same theme. Specifically, the main issue concerns how the studies on this theme emerge and continue to develop. It is then formulated into three main issues: how the construction of religious moderation is developed in Indonesia; how it is formulated into strategic policies in the higher education context; and how relevant the religious moderation program in the higher educations in Indonesia in the context of contemporary life is. By using a qualitative-library approach and content analysis, the finding shows that religious moderation or moderate Islam, which is believed to be Islam itself, is a moderate religious understanding and attitude. It is not extreme, is not either left or right; and is interpreted with four indicators: national commitment, tolerance, non-violence, and accommodative to local culture. From this stance, Indonesian Islamic moderation researchers propose various recommendations to be applied to specific education policies. In the practice, these recommendations are academically applied, both in formal and informal ways, according to the situations and conditions of the related higher education context. Moreover, recent studies have shown that several counter-radicalism strategies, through the moderation implemented in various higher educations, seem relevant in the higher education context.